MAKNA KONTEKSTUAL DALAM LAGU LUKAH GILO PADA MASYARAKAT KABUPATEN TEBO PROVINSI JAMBI (STRUKTURAL HERMENEUTIK) - Septi Rahmawati; Ade Rahima (Universitas Batanghari, 2019)
This research is aimed at describing contextual meaning in the song lukah gilo of Tebo Regency society Jambi city. This research is qualitative descriptive. The data is the lyric of lukah gilo song of Tebo regency society Jambi city (Hermeneutics structural). Meanwhile the technique of collecting data is observation, interview, and recording. The result of this research shows the description of how contextual meaning in the song lukah gilo of Tebo regency society Jambi city (hermeneutics structural), they are: (1) Contextual meaning on the song lyric of lukah gilo related with lexical meaning, (2) Contextual meaning which is related with situational context (place and time), (3) Contextual meaning which is related with belief, (4) Contextual meaning which is related with animism, (5) Contextual meaning which is related with faith. The contextual meaning in the song lukah gilo consists of 72 lines and dan 11 verses.